2008
DOI: 10.1016/j.pain.2007.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Patient training in cancer pain management using integrated print and video materials: A multisite randomized controlled trial ☆

Abstract: Standard guidelines for cancer pain treatment routinely recommend training patients to reduce barriers to pain relief, use medications appropriately, and communicate their pain-related needs. Methods are needed to reduce professional time required while achieving sustained intervention effectiveness. In a multisite, randomized controlled trial, this study tested a pain training method versus a nutrition control. At six oncology clinics, physicians (N=22) and nurses (N=23) enrolled patients (N=93) who were over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
101
0
12

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(113 citation statements)
references
References 29 publications
0
101
0
12
Order By: Relevance
“…In so far as these are supported by evidence the impact upon knowledge can be presumed and has been demonstrated in some cases (e.g. Syrjala et al, 2008). Individual trials of interventions designed to improve communication skills among nurses (Rask et al, 2009) and a nurse-delivered patient information support service (Passalacqua et al, 2009) did not lead to improved outcomes (perceived communication quality or satisfaction with knowledge) but in neither case was it clear that the intervention was successfully implemented.…”
Section: Resultsmentioning
confidence: 95%
“…In so far as these are supported by evidence the impact upon knowledge can be presumed and has been demonstrated in some cases (e.g. Syrjala et al, 2008). Individual trials of interventions designed to improve communication skills among nurses (Rask et al, 2009) and a nurse-delivered patient information support service (Passalacqua et al, 2009) did not lead to improved outcomes (perceived communication quality or satisfaction with knowledge) but in neither case was it clear that the intervention was successfully implemented.…”
Section: Resultsmentioning
confidence: 95%
“…Through the communication with the patient, respect for the patient's right to informed consent, and with the patient to develop care plans and care measures, thus improving the patient's treatment and care compliance, so that patients more easily adapt to the patient's role function (t = −14.66, P = 0.000); Studies have shown that: nurses on cancer patients with pain management education is more conducive to the patient to reduce the pain and pain medication use obstacles, improve the effectiveness of cancer pain management [9], In this study, in addition to active treatment of pain, but also to strengthen the nurses, patients and their families on the pain-related knowledge of education, improve the patient's cognitive function (t = −17.74, P = 0.000); In the process of palliative care, death education is strengthened, so that patients and their families establish the correct attitude and cognition of death, take a positive attitude to live and improve the social function of patients (t = −10.65, P = 0.000); All in all, after a se-ries of palliative care, the patient was fully cared for from the body and mind,…”
Section: Discussionmentioning
confidence: 99%
“…Three papers were focused on people with heart failure (Albert, Buchsbaum, & Li, 2007;Boyde et al, 2013;Veroff et al, 2012); two on those with cancer pain (Capewell, Gregory, Closs, & Bennett, 2010;Syrjala et al, 2008); and one each on people with sexual dysfunction following radical prostatectomy (Chambers et al, 2008); end-stage renal disease (Chiou & Chung, 2012); peripheral vascular disease (Collins, Krueger, Kroll, & Sharf, 2009); haemophilia related joint pain (Elander, Robinson, & Morris, 2011); and spinal cord injury (Hoffman et al, 2011).…”
Section: Intended Recipients Of the Interventionsmentioning
confidence: 99%
“…Only one of the interventions consisted entirely of audio-visual material and this was the only intervention delivered online (Hoffman et al, 2011). The remainder consisted of audio-visual content supplemented by written material (Capewell et al, 2010;Elander et al, 2011;Veroff et al, 2012), some also with professional led face-to-face education or support (Albert et al, 2007;Boyde et al, 2013;Collins et al, 2009;Syrjala et al, 2008), or telephone contact (Chambers et al, 2008;C -P Chiou & Chung, 2012).…”
Section: Multimedia Contentmentioning
confidence: 99%
See 1 more Smart Citation